A Comparison of Different Methods to Generate Tooth Surface Models Without Applying Ionizing Radiation for Digital 3-Dimensional Image Fusion With Magnetic Resonance Imaging–Based Data of the Head and Neck Region. Issue 6 (November 2015) - Traser, Louisa; Flügge, Tabea Viktoria; Burdumy, Michael; Kamberger, Robert; Richter, Bernhard; Hassepass, Frederike; Korvink, Jan Gerrit; Echternach, Matthias
Abstract : Objective: The 3-dimensional display of the vocal tract and teeth is necessary in numerous clinical and scientific contexts. Due to the different tissue properties this can only be achieved by combining different imaging techniques. A comparison of methods to record the tooth surface to create combined models of the vocal tract and teeth without applying ionizing radiation is displayed in this study. Methods: Four methods to record the tooth surface were compared concerning their clinical accuracy after combination with magnetic resonance imaging (MRI)–based vocal tract models. With 2 of the presented methods the information of the tooth surface was obtained from MRI data. With the other 2 methods, the tooth surface was captured using a digital and a conventional impression technique. Results: Impression techniques received the best rating results. Conclusions: The digital 3-dimensional image fusion of dental impression and MRI resulted in a virtual model of the vocal tract and teeth with a high clinical accuracy without applying ionizing radiation.